Peningkatan Kekuatan Otot Pasien Stroke Non Hemoragik dengan Hemiparese melalui Latihan Range of Motion (ROM) Pasif - Elsi Rahmadani; Handi Rustandi (Journal of Telenursing (JOTING), 2019)
This study aims to analyze the strength of muscle strength in patients with non- hemorrhagic stroke with hemiparese through Passive Range of Motion (ROM) exercises at Bengkulu Curup Hospital 2019. This research method uses the Quasi Experiment design of the pre and post test designs. The results of this study indicate the average value of pre-test and post-test muscle strength. increased in the intervention group and no increase in the control group. significant value (p = 0.008) in the intervention group and (p = 0.5) in the control group. Conclusion, there is the effect of Range of Motion exercise on the muscle strength of non-hemorrhagic stroke patients at ICU Curup General Hospital in 2019. Keywords: Muscle Strength, Range of Motion (ROM) Exercise